Antigens of Mycobacterium tuberculosis Stimulate CXCR6+ Natural Killer Cells - Choreño-Parra, José Alberto; Jiménez-Álvarez, Luis Armando; Muñoz-Torrico, Marcela; Ramírez-Martínez, Gustavo; Jiménez-Zamudio, Luis Antonio; Salinas-Lara, Citlaltepetl; García-Latorre, Ethel Awilda; Zúñiga, Joaquín (Frontiers in Immunology, 2020)
Natural killer (NK) cells participate in immunity against several pathogens by exerting cytotoxic and cytokine-production activities. Some NK cell subsets also mediate recall responses that resemble memory of adaptive lymphocytes against antigenic and non-antigenic stimuli. The C-X-C motif chemokine receptor 6 (CXCR6) is crucial for the development and maintenance of memory-like responses in murine NK cells. In humans, several subsets of tissue-resident and circulating NK cells with different functional properties express CXCR6. However, the role of CXCR6+ NK cells in immunity against relevant human pathogens is unknown. Here, we addressed whether murine and human CXCR6+ NK cells respond to antigens of Mycobacterium tuberculosis (Mtb). For this purpose, we evaluated the immunophenotype of hepatic and splenic CXCR6+ NK cells in mice exposed to a cell-wall (CW) extract of Mtb strain H37Rv. Also, we characterized the expression of CXCR6 in peripheral NK cells from active pulmonary tuberculosis (ATB) patients, individuals with latent TB infection (LTBI), and healthy volunteer donors (HD). Furthermore, we evaluated the responses of CXCR6+ NK cells from HD, LTBI, and ATB subjects to the in vitro exposure to CW preparations of Mtb H37Rv and Mtb HN878. Our results showed that murine hepatic CXCR6+ NK cells expand in vivo after consecutive administrations of Mtb H37Rv CW to mice. Remarkably, pooled hepatic and splenic, but not isolated splenic NK cells from treated mice, enhance their cytokine production capacity after an in vitro re-challenge with H37Rv CW. In humans, CXCR6+ NK cells were barely detected in the peripheral blood, although slightly significative increments in the percentage of CXCR6+, CXCR6+CD49a-, CXCR6+CD49a+, and CXCR6+CD69+ NK cells were observed in ATB patients as compared to HD and LTBI individuals. In contrast, the expansion of CXCR6+CD49a- and CXCR6+CD69+ NK cells in response to the in vitro stimulation with Mtb H37Rv was higher in LTBI individuals than in ATB patients. Finally, we found that Mtb HN878 CW generates IFN-γ-producing CXCR6+CD49a+ NK cells. Our results demonstrate that antigens of both laboratory-adapted and clinical Mtb strains are stimulating factors for murine and human CXCR6+ NK cells. Future studies evaluating the role of CXCR6+ NK cells during TB are warranted.